Endoscopic submucosal dissection of the pharyngeal region using anchored hemoclip with surgical thread: A novel method - Minami, Hitomi; Tabuchi, Maiko; Matsushima, Kayoko; Akazawa, Yuko; Yamaguchi, Naoyuki; Ohnita, Ken; Takeshima, Fuminao; Nakao, Kazuhiko (Endoscopy International Open, 2016)
Background and study aims: Endoscopic submucosal dissection (ESD) of the pharyngeal region has not been well accepted, although ESD of the gastrointestinal tract is a standard procedure for treating early cancers. However, early detection and treatment of pharyngeal cancers is highly beneficial because surgical resection can be highly invasive and cause serious cosmetic deformities, swallowing disorders, dysgeusia, and speech defects. On the other hand, application of an anchored clip with surgical thread during ESD of the gastrointestinal tract has been reported to be beneficial. This pilot case series reveals the usefulness and clinical feasibility of applying a clip with thread in ESD of the pharyngeal region.